Cloud Mobile Storage for Mobile Applications - Mourlin, Fabrice Pascal; Farinone, Jean-Marc (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The data storage in mobile cloud computing domain is an important subject because of the large amount of data devices can provide. Different kinds of sensors retrieve information and send them to data storages. But the storage location can move even dynamically during their uses. So, these changes must be managed at runtime. In the other part, Android devices are good computers to acquire information and send them to a storage area. These devices are well-known, ergonomic and useful machines sorely used. In this paper, we present a software architecture from Android devices to Cloud storage areas to put down data when the data stores are dynamically moving. The different parts of these distributed applications are built around Android with JSON messages for REST services and moving NoSQL databases in the Google app engine. The exchanges between the cloud and the Android devices use the Google Cloud Messaging (GCM) protocol. Furthermore, even without network access, the saving is made locally in the smartphone. The synchronization with distant databases is automatically made when the network becomes again available.